Synthesis and Characterization of starch-maleate-chitosan nanocomposite film - Ng, Wan Yin (Universiti Malaysia Sarawak, UNIMAS, 2013)
Starch-maleate-chitosan (SMC) nanocomposite films were prepared from a mixture of starch-maleate and chitosan nanoparticles. The effect of components ratio on the physical and antibacterial properties of prepared films were investigated by FTIR, SEM, water absorbency and zone inhibition test. FTIR revealed the bonding between starch-maleate and chitosan nanoparticles. The water absorbency of SMC nanocomposite films were showed increased as chitosan nanoparticles amount increased. This was due to the chitosan itself was hydrophilic and with poor-water barrier characteristic. The nanocomposite films had shown inhibition effect against E. coli when investigated qualitatively by zone inhibition method. However, increase in chitosan nanoparticles volume did not significantly increased the antibacterial effect.